A systematic review of the pathological determinants of outcome following resection by pelvic exenteration of locally advanced and locally recurrent rectal cancer. (August 2022) - Gould, Laura E.; Pring, Edward T.; Drami, Ioanna; Moorghen, Morgan; Naghibi, Mani; Jenkins, John T.; Steele, Colin W.; Roxburgh, Campbell SD.
Abstract: Background: Despite multimodal therapy 5–15% of patients who undergo resection for advanced rectal cancer (LARC) will develop local recurrence. Management of locally recurrent rectal cancer (LRRC) presents a significant therapeutic challenge and even with modern exenterative surgery, 5-year survival rates are poor at 25–50%. High rates of local and systemic recurrence in this cohort are reflective of the likely biological aggressiveness of these tumour types. This review aims to appraise the current literature identifying pathological factors associated with survival and tumour recurrence in patients undergoing exenterative surgery. Methods: A systematic review was carried out searching MEDLINE, EMBASE and COCHRANE Trials database for all studies assessing pathological factors influencing survival following pelvic exenteration for LARC or LRRC from 2010 to July 2021 following PRISMA guidelines. Risk of bias was assessed using QUIPS tool. Results: Nine cohort studies met inclusion criteria, reporting outcomes for 2864 patients. Meta-analysis was not possible due to significant heterogeneity of reported outcomes. Resection margin status and nodal disease were the most commonly reported factors. A positive resection margin was demonstrated to be a negative prognostic marker in six studies. Involved lymph nodes and lymphovascular invasion also appear to be negative prognostic markers with tumour stage to be of lesser importance. No studies assessed other adverse tumour features that would not otherwise be included in a standard histopathology report. Conclusion: Pathological resection margin status is widely demonstrated to influence disease free and overall survival following pelvic exenteration for rectal cancer. With increasing R0 rates, other adverse tumour features must be explored to help elucidate differences in survival and potentially guide tailored oncological treatment. Highlights: Resection margin status influences survival following pelvic exenteration. Lymph node involvement and venous invasion are also negative prognostic markers. Other adverse tumour features must now be explored to explain survival differences.